Forced Identity Performances, Self‐Identification, the Material, and Ballotee Bevin Boys in WWII UK 1943‐1948: 'An Experience I Would Not Have Had, or Chosen'. Issue 4 (2nd December 2022) - Thompson, Scott
Abstract: This manuscript examines the relationship between forced, or required, identity performances, self‐identification, and the material. It tests core premises of identity formation within the performativity literature against the lived experiences of 'Ballotee Bevin Boys' ‐ coal mining conscripts managed under the UK's WWII National Registration and Ministry of Labour and National Service program. Data were drawn from fifty‐eight personal accounts of Ballotee Bevin Boys and analyzed to identify core themes around identity and performance by means of a narrative analysis. Multiple regression analyses then found that the quantity of i) narrative statements of self‐identification as a Bevin Boy, and ii) narrative statements of the material, could be predicted based on the prevalence of narratives of institutionally forced performances, and individual performances of resistance. These results support the claim that performances required of Ballotee Bevin Boys did sediment into their understandings of self, regardless of their individual intention or desire to be a Bevin Boy – even in cases of active resistance against this externally applied category. These findings support a theorization of identity formation and the material which decenters the role of the intention of the performing individual, instead, placing greater emphasis on institutional categories and their enforcement.